Clinical significance of B7-H4 expression in matched non-small cell lung cancer brain metastases and primary tumors - Li, Zhen-ye (Dove Medical Press, 2013)
BACKGROUND: B7-H4, a member of the inhibitory B7 family, is shown to have a profound inhibitory effect on the proliferation, activation, cytokine secretion, and development of cytotoxicity of T cells and may be involved in immune evasion in cancer patients. Although B7-H4 expression has been detected in non-small cell lung cancer (NSCLC), there are no published reports on the expression of B7-H4 in brain metastases from NSCLC. METHODS: We examined the expression of B7-H4 by immunohistochemistry in 49 cases of brain metastatic NSCLC, 18 cases of matched primary NSCLC, and 20 cases of NSCLC patients who had neither brain metastases nor other distant metastases. RESULTS: B7-H4 was highly expressed in 20 (40.8%) out of 49 brain metastases and two (11.1%) out of 18 matched primary tumors. The expression of B7-H4 in brain metastases appeared to be significantly higher than their matched primary tumors (P = 0.016). We also found that patients with high B7-H4 expression in their primary NSCLC have a higher risk of developing brain metastases (P = 0.022). Univariate analyses showed that median overall survival was significantly shorter in patients with high B7-H4 expression in brain metastases (P = 0.002). Multivariate analyses showed that B7-H4 was a significant independent prognostic indicator (P = 0.003). CONCLUSION: NSCLC patients with high B7-H4 expression may benefit from aggressive treatment and close surveillance. Furthermore, our study suggests that B7-H4 may play an important role in the metastatic process of NSCLC and is promising to be a new immune checkpoint molecule for future antitumoral immunotherapy.